Islamisasi Tanah Jawa Abad ke-13 M dalam Kitab Musarar Karya Syaikh Subakir - Siti Rumilah; Indah Wulandari; Ainiyah Syafitri; Dina Maulidia; Hilmi Musyafa; Nur Laila Zulfa; Wan Khairina Hanim (Program Studi Sastra Indonesia UIN Sunan Ampel Surabaya, 2020)
Kitab Musarar is one of the famous works of Syaikh Subakir described the condition of Java both before and after the arrival of Syaikh Subakir in the 13th century in Java on the mission of Islamization. This study uses a qualitative research method based on the Kitab Musarar which has been rewritten in an old spelling Indonesian translation printed book titled Kitab Musarar Syaikh Subakir-Asal Muasal Tanah Jawa karya Sukri (2011) and the book of Melacak Jejak Syaikh Subakir: Riwayat Penumbalan Tanah Jawa dan Walisanga Generasi Pertama written by Romadhon (2017). The results of this study are: (1) The existence of the early history of the world until the entry of Islam in Java in the 13th century in the Kitab Musarar by Syaikh Subakir, (2) The existence of figures who played a role of rukyat in Java in the 13th century based on the Kitab Musarar by Syaikh Subakir, and (3) The story of sangsara era and Ratu Adil profil in the Kitab Musarar by Syaikh Subakir. Overall, it can be seen that there are traces of Javanese Islamization brought by Syaikh Subakir in the 13th century based on the Kitab Musarar.